Portrayal of Men in Damilare Kuku Nearly all Men in Lagos. - Arineitwe, Bridget (Kabale University, 2025)
The study was about the portrayal of men in Damilare Kuku nearly all men in Lagos are mad. It was guided by the following study objectives; to examine the portrayal of men in the novel including their characters, actions, and how they are seen in the society in Nearly All Men in Lagos Are Mad, to analyze the dominant masculine norms and stereotypes presented in the novel Nearly All Men in Lagos Are Mad and to explore how the novel represents men's relationship with women in families or outside families in Lagos. The study employed qualitative data to gather information about the Portrayal of men in Nearly All men in Lagos are Mad by Damilare Kuku. The study utilized both quantitative and qualitative data collection and analysis methods. Criteria for text selection were grounded on the relevance, authenticity, and analytical depth of the materials chosen for study. By adhering to these criteria during text selection, the researcher created a robust framework for analyzing how men are portrayed in Damilare Kuku’s work while situating their findings within broader discussions about gender roles in Lagos society. The study considered a population of 76 literature students and 4 Literature Lecturers at Kabale University. The sample size of 66 respondents was chosen and represented the whole study population. Close reading and textual analysis of the textual were used. The study employed questionnaires, key informant interviews, and observation methods. A questionnaire consisted of a series of questions on the existing system and the user requirements for the proposed database system. In this method, several relevant questions based on the study objectives were distributed to 3rd-year literature students and a few selected literature students from the second year at Kabale University. During processing, the data was edited and proofread. This ensured a clear and easy presentation of research findings. After thorough sorting, the data was entered into a computer for analysis using Microsoft Word and Excel. The novel critiques dominant masculine norms prevalent in Nigerian society, particularly those that dictate behavior, success, and emotional expression among men. Kuku uses humor and satire to expose the absurdity of these stereotypes while simultaneously illustrating how they constrain men’s lives. The study recommended academic research focused on gender representation in contemporary literature, particularly within African contexts. Such studies can provide deeper insights into how masculine stereotypes evolve over time and their impact on society